Vpliv treninga moci na mišicni moment kvadricepsa in hamstringa pri mladih nogometaših - Yilmaz, A. K.; Kabadaya, M.; Bostanci, Ö.; Yilmaz, C.; Mayda, M. H. (Kinesiologia Slovenica, 2020)
The purpose of the present study was to investigate the effect of eight week core strength training (CST) on quadriceps and hamstring muscle strength and H/Q ratio. The study included a total of 20 young soccer players, 10 in the experimental group (EG) and 10 in the control group (CG). Isokinetic knee strength measurements at angular velocities of 60°sec-1, 180°sec-1 and 240°sec-1 were performed on the subjects. Independent sample t-test and 2x2 ANOVA test were used for statistical analysis. No significance was found between the pre-test results of both EG and CG (p>0.05). In post-test results, a difference was found in favour of EG group in RPM 60o EX value (p<0.05). When the pre-test and post-test results of the groups were compared separately, a significant difference was found in RPM 60o EX, LPM 180o EX and LPM 240o EX parameters in EG (p<0.05). A significant progress was found in LPM 180o EX, LPM 180o FLX and LPM 240o FLX values in CG (p<0.05). It was found that CST applied on young soccer players affected knee isokinetic strength in different velocity and this effect caused significance especially in different angular speeds of EX phase. In addition, although significant progress was not observed in all parameters in EG after CST, it was found that there weren`t decreases in any parameters and at least strength was maintained.